Challenges of Accessing and Using Rehabilitation Services in People With Autism Spectrum Disorder: A Systematic Review - Mohammad Saeed Khanjani; Kianoush Abdi; Mahta Alsadat Aarabi (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: One of the essential needs of patients with Autism Spectrum Disorder (ASD) and their families is the rehabilitation services to improve patients' performance in social interactions and communication. However, access and use of these services pose many challenges for patients with ASD and service providers. This study systematically reviews the challenges of access and use of rehabilitation services for patients with ASD. Materials & Methods: This is a systematic review of the articles published from 2010 to 2020 in Persian and English on the challenges of accessing and using rehabilitation services for patients with ASD. The search was conducted in online databases of Google Scholar, PubMed, Scopus, ProQuest, Science Direct, SID, and MagIran using the keywords of "challenge", "utilization", "accessibility", "rehabilitation", "healthcare", and "autism". The initial search yielded 142 articles. After checking their titles, 102 articles were removed because they were irrelevant or duplicates, and 40 remained. Finally, 14 studies were selected for the review after checking their abstracts and considering the inclusion criteria. Results: In general, due to the nature of ASD, patients and their families have many challenges in accessing and using rehabilitation services. Their essential challenges were high costs of services, insufficient insurance coverage, lack of parental involvement in healthcare, scarcity of some essential services, lack of access to specialists in ASD, no government support, long waiting times, no transportation, lack of information of parents about how to access the required services, heterogeneity of services provided in different centers, inefficiency in diagnosing and screening people with ASD, lack of rehabilitation monitoring, incoordination between autism centers, challenges related to the structure and maintenance of services, and low manpower of service providers. Conclusion: People with ASD face several challenges in accessing and using rehabilitation services. Our study results can be helpful for the effective use of rehabilitation services by these patients, improving their living conditions, and ultimately their quality of life. Recognizing these challenges can pave the way for policymakers, intervention managers, and planners to take more effective steps for providing rehabilitation services to patients with ASD as their human rights. The authorities should pay more attention to existing resources, adopt and implement the necessary programs, solve the identified challenges, and reform the administrative structures of autism rehabilitation.